Exploring the understanding, role and participation of Small and Medium Enterprises (SMEs) on digital economy in Malaysia - Rahman, Maya Puspa; Senusi, Nurfatihah (Malaysian Consumer and Family Economics Association, 2018)
This study explores the understanding, role and participation of the SMEs on the digital economy, in line with the aspiration by the Malaysian government to have higher growth contribution coming from this segment. The primary data is collected from a semi-structured interview with six SMEs around Klang Valley from various industries, and the analysis is conducted using coding and thematic analysis. Most of the SMEs interviewed are aware of the importance of online presence but lack the understanding of its contribution towards the digital economy. While a high number of them are ready to embrace technology-driven tools for sales, several others are still quite sceptical and facing difficulties in related cost management. This paper aims to offer specific insights from the SMEs on the digital economy and Malaysia's move towards adopting the relevance of the fourth industrial revolution. It also identifies some of the issues to be tackled by the government to have more SMEs participation in the Malaysian digital economy.